PENGARUH KONSELING GIZI PADA IBU TERHADAP ASUPAN ZAT GIZI DAN STATUS GIZI BADUTA STUNTING - Diba, Nadia Farah; Tamtomo, Didik Gunawan; Sumardiyono, Sumardiyono (Poltekkes Kemenkes Bandung, 2024)
The problem of stunting occurs because children are malnourished during 1000 days of life, characterized by shorter height compared to children of the same age. Various factors cause stunting, and lack of maternal nutritional knowledge can affect maternal nutritional behavior in improper feeding. Nutrition counseling interventions were carried out for mothers so that changes in maternal nutritional behavior occur for the better. This study aimed to analyze the effect of nutrition counseling on maternal nutrition knowledge and attitudes, nutrient intake, and nutritional status of stunted toddlers. This study used a randomized control trial, which was located in 5 health centers including Puskesmas Kedungkandang, Arjuno, Ciptomulyo, Dinoyo, and Polowijen Malang City, in June-August 2023. Respondents were mothers of stunted children aged 6-24 months. The number of respondents in the treatment and control groups was 44 people each group. Statistical analysis used was the Paired Sample T-test, Wilcoxon Test, Independent Sample T-test, and Mann-Whitney U test. There was a significant difference in the mean between the two groups on nutritional knowledge (p=0.000), respondents' attitudes (p=0.000), nutrient intake of energy (p=0.000), carbohydrate (p=0.021), and protein (p=0.000), and nutrition status of stunted toddlers (p=0.000). Nutrition counseling can improve nutrition knowledge, maternal attitudes, nutrient intake energy, carbohydrates, and protein, and nutrition status of stunted toddlers.